Estimating leaf area in velvetleaf (Limnocharis flava) and kangkong (Ipomea aquatica): a precise and non-destructive approach for wetland vegetables - Riyanti, Anggrika; Lakitan, Benyamin; Imanudin, Momon Sodik; Yazid, Muhammad (Universitas Padjadjaran, 2026)
Developing a leaf-area estimation model for vegetable cultivars in wetlands is essential to optimizing agricultural cultivation practices. This study aims to develop a non-destructive model for leaf area estimation in wetland vegetable cultivars (velvetleaf (Limnocharis flava) and kangkong (Ipomoea aquatica)) using regression-based models. The plants were cultivated in a wetland system. Measurements of leaf length and width were taken on all leaves of each plant, using the product of length and width (L×W) as predictor. The regression models for estimating leaf area were adjusted from linear, zero-intercept linear, quadratic, and power. The optimal model was evaluated using the determination coefficient (R2) and the Root Mean Square Error (RMSE). The results showed that the most reliable regression model for estimating velvetleaf leaf area was linear regression with the equation y = 0.881LW - 7.615 (R2 = 0.954; RSME = 7.916), and the power model for kangkong leaf area, with the equation y = 0.9407LW0.9309 (R2 = 0.970; RSME = 1.695). Differences in leaf shape among plant species result in different accuracies of leaf area estimation models. Thus, the model should be useful to guide future research and practical applications in monitoring leaf growth and determining harvest time.